Trichoderma harzianum cerato‐platanin enhances hydrolysis of lignocellulosic materials. Issue 4 (9th June 2021) - Pennacchio, Anna; Pitocchi, Rossana; Varese, Giovanna Cristina; Giardina, Paola; Piscitelli, Alessandra
Summary: Considering its worldwide abundance, cellulose can be a suitable candidate to replace the fossil oil‐based materials, even if its potential is still untapped, due to some scientific and technical gaps. This work offers new possibilities demonstrating for the first time the ability of a cerato‐platanin, a small fungal protein, to valorize lignocellulosic Agri‐food Wastes. Indeed, cerato‐platanins can loosen cellulose rendering it more accessible to hydrolytic attack. The cerato‐platanin Th CP from a marine strain of Trichoderma harzianum, characterized as an efficient biosurfactant protein, has proven able to efficiently pre‐treat apple pomace, obtaining a sugar conversion yield of 65%. Moreover, when used in combination with a laccase enzyme, a notable increase in the sugar conversion yield was measured. Similar results were also obtained when other wastes, coffee silverskin and potato peel, were pre‐treated. With respect to the widespread laccase pre‐treatments, this new pre‐treatment approach minimizes process time, increasing energy efficiency. Abstract : The cerato‐platanin ThCP from a marine strain of Trichoderma harzianum is able to efficiently pre‐treat three Agro‐food wastes endowed with different lignin and carbohydrate contents. ThCP and a Pleurotus ostreatus laccase synergistically work in the pre‐treatment process, allowing an almost complete sugar recovery from the three Agro‐food wastes.